2021
DOI: 10.3389/fnins.2021.683153
|View full text |Cite
|
Sign up to set email alerts
|

Is Peripheral Motion Detection Affected by Myopia?

Abstract: PurposeThe current study was to investigate whether myopia affected peripheral motion detection and whether the potential effect interacted with spatial frequency, motion speed, or eccentricity.MethodsSeventeen young adults aged 22–26 years participated in the study. They were six low to medium myopes [spherical equivalent refractions −1.0 to −5.0 D (diopter)], five high myopes (<-5.5 D) and six emmetropes (+0.5 to −0.5 D). All myopes were corrected by self-prepared, habitual soft contact lenses. A four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Thorn et al (2016) measured peripheral contrast detection thresholds binocularly at 8, 17, and 30° eccentricities and found no significant difference between myopes and emmetropes. Wei et al (2021) found motion detection thresholds were negatively correlated with the degree of myopia for low spatial frequency targets at 20° eccentricity. In this study, we applied the Bayesian adaptive qCSF procedure and compared the contrast sensitivity functions of myopes and emmetropes in peripheral vision.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Thorn et al (2016) measured peripheral contrast detection thresholds binocularly at 8, 17, and 30° eccentricities and found no significant difference between myopes and emmetropes. Wei et al (2021) found motion detection thresholds were negatively correlated with the degree of myopia for low spatial frequency targets at 20° eccentricity. In this study, we applied the Bayesian adaptive qCSF procedure and compared the contrast sensitivity functions of myopes and emmetropes in peripheral vision.…”
Section: Discussionmentioning
confidence: 84%
“…Multiple articles have demonstrated that visual functions differ in different parts of the visual field in myopia and the emmetropia, with visual acuity in the nasal and superior retinal regions being better than that in the temporal and inferior regions in myopia and emmetropia groups (Ehsaei et al, 2013). Wei et al (2021) found significant correlation between myopia severity and motion detection thresholds in the nasal and superior visual field at 20 • . Kuo et al (2018) found significant correlations between Dmin task performance and myopia severity in the superior and temperal 10.3389/fnins.2022.971009…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Static and dynamic contrast sensitivity were evaluated at 20° eccentricity 32,33 . The optotype stimulus was a phase‐shifted grating within a two‐dimensional Gaussian window—Gabor stimulus, displayed at 20° eccentricity and randomly presented in one of the four quadrants of the visual field (nasal, temporal, superior and inferior; Figure 1) for 200 ms in each trial.…”
Section: Methodsmentioning
confidence: 99%
“…Static and dynamic contrast sensitivity were evaluated at 20° eccentricity. 32,33 The optotype stimulus was a phaseshifted grating within a two-dimensional Gaussian window-Gabor stimulus, displayed at 20° eccentricity and randomly presented in one of the four quadrants of the visual field (nasal, temporal, superior and inferior; Figure 1) for 200 ms in each trial. The test distance was 0.55 m. In this experiment, a four-option forced-choice task was used, which required participants to focus and fixate on a cross at the centre of the screen (Figure 1).…”
Section: Peripheral Contrast Thresholdsmentioning
confidence: 99%